Sistem Informasi Peminjaman Ruangan Fakultas MIPA Universitas Tanjungpura - Renny Puspita Sari; Ibnur Rusi; Tasha Safira Putri (Ikatan Ahli Informatika Indonesia, 2020)
The room loan information system at the Faculty of Mathematics and Natural Sciences, Tanjungpura University was built because the process of borrowing space at the Faculty of Mathematics and Natural Sciences was not yet using technology. Need help that is better than expected, both from the borrower and those who have lending facilities, there are still those who ask for a loan approval letter, the amount of lending data can help redundancies based on room lending information for a long time, the lending process, must be approved by various party. In this research, as a first step in developing the system, a system analysis using the PIECES framework is used as an analysis of the functional requirements of the system to see the weaknesses of conventional old systems compared to new systems using technology. From this analysis the system design is made using UML. Furthermore, the design that has been made will be implemented into the PHP Programming Language. The final results of this study will display the room usage schedule, the process of filing a room loan, the loan report and the notification flow which are expected to provide complete and efficient information related to room lending that must be searched for the long and difficult process of borrowing the room and help assist the search process in the borrower room online and can be computerized well.